Proximal Tubule–Specific Deletion of the NHE3 (Na+/H+ Exchanger 3) Promotes the Pressure-Natriuresis Response and Lowers Blood Pressure in Mice. Issue 6 (December 2018) - Li, Xiao C.; Soleimani, Manoocher; Zhu, Dongmin; Rubera, Isabelle; Tauc, Michel; Zheng, Xiaowen; Zhang, Jianfeng; Chen, Xu; Zhuo, Jia L.
Abstract : The present study directly tested the hypothesis that deletion of the NHE3 (Na + /H + exchanger 3) selectively in the proximal tubules of the kidney lowers basal blood pressure by increasing the pressure-natriuresis response in mice. Adult male and female, age-matched wild-type (WT) littermates and proximal tubule–specific NHE3 knockout mice (PT- Nhe3 −/− ; n=6–16 per group) were studied for (1) basal phenotypes of electrolytes and pH, blood pressure, and kidney function; (2) the pressure-natriuresis response using the mesenteric, celiac, and abdominal arterial occlusion technique; and (3) the natriuretic responses to acute saline expansion (0.9% NaCl, 10% body weight, intraperitoneal) or 2-week of 2% NaCl diet. Under basal conditions, PT- Nhe3 −/− mice showed significantly lower systolic, diastolic, and mean arterial blood pressure ( P <0.01) than WT mice ( P <0.01). PT- Nhe3 −/− mice also exhibited significantly greater diuretic ( P <0.01) and natriuretic responses than WT mice ( P <0.01), without altering 24-hour fecal Na + excretion, plasma pH, Na +, and bicarbonate levels. In response to increased renal perfusion pressure by 30 mm Hg, the pressure-natriuresis response increased 5-fold in WT mice ( P <0.01), but it increased 8-fold in PT- Nhe3 −/− mice ( P <0.01). In response to 10% acute saline expansion or 2-week 2% NaCl diet, more pronounced natriuretic responses were demonstrated in PT- Nhe3 −/− than WT mice ( P <0.01). Our results support the scientific premise and physiological relevance that NHE3 in the proximal tubules plays an essential role in maintaining basal blood pressure homeostasis, and genetic deletion of NHE3 selectively in the proximal tubules of the kidney lowers blood pressure by increasing the pressure natriuretic response. Abstract : Supplemental Digital Content is available in the text.